Radio frequency interference (RFI) in solar monitoring / Norsuzian binti Mohd Anim - Mohd Anim, Norsuzian (2013)
Radio frequency interference (RFI) distorted the detection of solar bursts from ground based observation. By using Compact Astronomical Low-cost Low-frequency Instrumentation Spectrometer Transportable Observatory (CALLISTO), the physical characteristic of solar burst, the structures of sun, velocity of solar flares are being studied. The results are useful for space weather studies and to protect the communication satellites and the space station. The interference from terrestrial sources of 13 chosen CALLISTO station all around the world are being identified. The objective is to understand the RFI’s impacts to the detection of solar monitoring from ground base. This study found that the highest interference 100% is from the broadcasting system. This study additionally discusses the efficiency of selecting good frequency spectrum window to minimize this RFI so that solar monitoring observation can be at the most efficacious impact